The use of very low‐calorie diets in subjects with obesity complicated with nonalcoholic fatty liver disease: A scoping review - Grant J. Herrington; Joshua J. Peterson; Linhai Cheng; Benjamin M. Allington; Renato D. Jensen; Heather S. Healy; Marcelo L. G. Correia (Obesity Science & Practice, 2022)
Abstract This scoping review synthesizes the existing research on the use of very low‐calorie diets (VLCDs) in subjects with nonalcoholic fatty liver disease (NAFLD) and end‐stage liver disease (ESLD). 19 studies were included, of which 5 were clinical trials, 11 were cohort studies, 1 was a case‐control study, and 2 were case series totaling 968 subjects. About 17 studies were focused on patients with NAFLD while the two case series described in patients with ESLD on the transplant list or post‐liver transplant. Six studies included subjects managed with VLCDs prior bariatric surgery. Most studies were short term and demonstrated acute improvement of diverse liver biomarkers including liver function tests, indices of hepatosteatosis and reduction in liver size. Adherence rates in these studies were between 69% and 93%. Eight studies did not report any adverse events and four subjects were reported to have discontinued VLCD due to adverse effects in two different studies. Aggregated adverse events were mild. Treatments based on VLCD in subjects with NAFLD seem to be safe and tolerable but can result in mild adverse effects. The findings of this scoping review suggest that the use of VLCD in patients with obesity complicated with NAFLD and potentially in ESLD appear to be effective to induce weight loss and to acutely reduce hepatosteatosis.